Patterns of major divergence between the internal transcribed spacers of ribosomal DNA in Xenopus borealis and Xenopus laevis, and of minimal divergence within ribosomal coding regions. - Furlong, J C (1983)
We have determined the nucleotide sequences of the two internal transcribed spacers, the adjacent ribosomal coding sequences and the boundary between the external transcribed spacer and the 18S coding sequence in a cloned ribosomal transcription unit from Xenopus borealis. The transcribed spacers differ very extensively from those of X. laevis. Nevertheless, embedded in the internal transcribed spacers are several short sequence elements which are identical between the two species. These conserved elements are laterally displaced by substantial distances in the X. borealis sequence with respect to that of X. laevis. These relative displacements imply that insertions and deletions have played a major role in transcribed spacer divergence in Xenopus. This in turn implies that large regions of the transcribed spacers do not play a sequence-specific role in ribosome maturation. In contrast, the sequenced parts of the ribosomal coding regions, which encompass 670 nucleotides, differ at only three points from the corresponding sequences in X. laevis, each by a single substitution. These substitutions are readily accommodated by current models for rRNA higher order structure.